Feasibility Analysis of Industrial High-Temperature Heat Pumps in Greece - Evangelos Bellos; Dimitra Gonidaki; Antonios Nazos; John K. Kaldellis (Applied Sciences)
The high-temperature heat pump is a favorable technology for aiding the decarbonization of the industrial sector through its electrification. It can produce useful heat up to the range of 100 °C to 200 °C; however, additional steps are needed to develop reliable and highly efficient systems. The objective of this investigation is the systematic analysis of different operating cases of high-temperature heat pumps for industrial process heat production, from 100 °C up to 180 °C, exploiting waste heat from 50 °C to 100 °C. Moreover, the case of the ambient-source heat pump is studied for different process heat temperatures using an hourly-based analysis of the Greek climate conditions. The final results are evaluated based on energy, economic and environmental criteria to estimate the feasibility of industrial high-temperature heat pumps from a holistic perspective. The results indicate system sustainability for process heat temperatures up to 160 °C and for the scenarios with higher waste heat input temperatures. For the ambient-source high-temperature heat pump, the economically viable scenario was found only for the case of heat production at 100 °C due to the significant efficiency reduction at higher temperatures. Specifically, the COP was found to be up to 1.924 for the ambient-source heat pump and up to 3.285 for the waste heat source heat pump for a waste heat source at 75 °C. The levelized cost of heating was found to be in the range of 0.0562 to 0.0977 EUR/kWh for the ambient-source heat pump and in the range of 0.0377 to 0.0869 EUR/kWh for the waste heat source heat pump. Lastly, both waste heat- and ambient-source-driven heat pumps lead to CO2 emission reductions compared to the scenario based on a conventional natural gas boiler.